2018
DOI: 10.1080/0142159x.2018.1435859
|View full text |Cite
|
Sign up to set email alerts
|

Growth of the James Cook University Medical Program: Maintaining quality, continuing the vision, developing postgraduate pathways

Abstract: Postgraduate pathways are an important priority. Regional training hubs are being developed to support local pipelines into specialty practice. Queensland's Rural Generalist Pathway provides an incentivised pathway to rural practice while Generalist Medical Training provides a local training pipeline into general practice and rural medicine. As these initiatives mature, communities should benefit as JCU and other Australian programs continue to address local workforce needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 8 publications
0
21
0
Order By: Relevance
“…Having a critical mass of doctors was a key issue enabling balanced and flexible work schedules to be modelled by supervisors resulting in attracting and retaining registrars and a sustainable remote supervision model. Critical mass could be developed encouraging groups of medical students and registrars to train together, including early and repeated training opportunities in remote communities as multiple placements throughout medical school, in the early postgraduate years, and during vocational training [22]. Retaining remote supervisors through their careers requires upskilling provisions and innovative work and supervision models to promote career diversification whilst sustaining work in the same remote community [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Having a critical mass of doctors was a key issue enabling balanced and flexible work schedules to be modelled by supervisors resulting in attracting and retaining registrars and a sustainable remote supervision model. Critical mass could be developed encouraging groups of medical students and registrars to train together, including early and repeated training opportunities in remote communities as multiple placements throughout medical school, in the early postgraduate years, and during vocational training [22]. Retaining remote supervisors through their careers requires upskilling provisions and innovative work and supervision models to promote career diversification whilst sustaining work in the same remote community [28].…”
Section: Discussionmentioning
confidence: 99%
“…Rural-based GP training has been shown to increase the likelihood of GPs practising in these areas for at least five years [17]. Other research has shown that both rural background [18–20] and extended rural placements during medical school [21, 22] positively influence rural practice in early career. However, there is very little contextual information about the rich range of background factors related to working and undertaking supervised postgraduate medical training in such communities, making it hard to implement solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Students who participate in undergraduate rural initiatives may achieve preference for postgraduate rural training places [ 2 ]. A well-known rural pathway is the Queensland Rural Generalist Program (QRGP), which attracts, trains and supports a medical workforce for smaller rural hospitals [ 17 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…These specific relationships included personal-professional, clinician-patient, university-health service and government-community. For communities in particular, contributing to the selection of doctors, health governance, teaching, and welcoming and supporting doctors and students during community placements are essential for symbiotic medical education to occur [ 17 ]. Symbiotic relationships may increase patient centred care [ 40 ] and workforce recruitment [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation